2023
DOI: 10.1007/s00134-022-06949-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an intensive care telehealth programme to improve process quality (ERIC): a multicentre stepped wedge cluster randomised controlled trial

Abstract: Purpose Supporting the provision of intensive care medicine through telehealth potentially improves process quality. This may improve patient recovery and long-term outcomes. We investigated the effectiveness of a multifaceted telemedical programme on the adherence to German quality indicators (QIs) in a regional network of intensive care units (ICUs) in Germany. Methods We conducted an investigator-initiated, large-scale, open-label, stepped-wedge cluster randomised co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Contrary to our initial hypothesis and other published data [36] we found that COVID-19 patients in the surge ICUs displayed higher rates of EM and higher levels of IMS. In our opinion the following factors may have influenced the focus on topics like EM and the results: (1) Authors of this paper who are established researchers in the field of early mobilisation participated in the teaching and were responsible for part of the surge ICUs, (2) early reports of long-lasting deep sedation with benzodiazepines and nearly no EM stimulated discussion to provide care according to our 10 quality indicators of intensive care medicine which includes EM and (3) intensivists of our hospital provided telemedicine care consultations to all hospitals in Berlin treating critically ill COVID-19 patients based again on the 10 quality indicators [37] . These may have had more influence on the surge ICUs since the multiprofessional critical care teams had not worked together before and allowed new workflows to be established with integration of the recommendations provided.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our initial hypothesis and other published data [36] we found that COVID-19 patients in the surge ICUs displayed higher rates of EM and higher levels of IMS. In our opinion the following factors may have influenced the focus on topics like EM and the results: (1) Authors of this paper who are established researchers in the field of early mobilisation participated in the teaching and were responsible for part of the surge ICUs, (2) early reports of long-lasting deep sedation with benzodiazepines and nearly no EM stimulated discussion to provide care according to our 10 quality indicators of intensive care medicine which includes EM and (3) intensivists of our hospital provided telemedicine care consultations to all hospitals in Berlin treating critically ill COVID-19 patients based again on the 10 quality indicators [37] . These may have had more influence on the surge ICUs since the multiprofessional critical care teams had not worked together before and allowed new workflows to be established with integration of the recommendations provided.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a secondary analysis of the multicenter, stepped-wedge cluster-randomized controlled Enhanced Recovery after Intensive Care (ERIC) trial (ClinicalTrials.gov: NCT03671447) (32, 33). ERIC was approved by the Institutional Review Board of Charité—Universitätsmedizin Berlin (EA1/006/18) on January 26, 2018.…”
Section: Methodsmentioning
confidence: 99%
“…ERIC was approved by the Institutional Review Board of Charité—Universitätsmedizin Berlin (EA1/006/18) on January 26, 2018. The presented analysis is original, has not been published before, adhered to the ethical standards of the Declaration of Helsinki from 1964 and its later amendments, and adhered to the Transparent Reporting of multivariable predication model for Individual Prognosis Or Diagnosis (TRIPOD) statement ( Supplement A , http://links.lww.com/CCM/H251) (33).…”
Section: Methodsmentioning
confidence: 99%
“…One peer-to-peer approach involving an interdisciplinary team of healthcare professionals, called the ‘hub-and-spoke model,’ facilitates live audio–video interaction at the bedside from a tertiary hospital to remote care providers to assist remote-site physicians in treating challenging cases. 3 The ‘hub-and-spoke model’ is a multiprofessional peer-to-peer approach involving an interdisciplinary team of doctors, nurses and allied healthcare professionals under the hybrid model, which combines teleconsultations with training and educational activities. It also enables the delivery of telemedical services across national borders, 4 which offers solutions to clinical questions and promotes the exchange of knowledge and experience about the novel infectious disease between healthcare professionals on a global level.…”
mentioning
confidence: 99%
“…Different telemedical models exist in the context of acute care. One peer-to-peer approach involving an interdisciplinary team of healthcare professionals, called the ‘hub-and-spoke model,’ facilitates live audio–video interaction at the bedside from a tertiary hospital to remote care providers to assist remote-site physicians in treating challenging cases 3. The ‘hub-and-spoke model’ is a multiprofessional peer-to-peer approach involving an interdisciplinary team of doctors, nurses and allied healthcare professionals under the hybrid model, which combines teleconsultations with training and educational activities.…”
mentioning
confidence: 99%